Of Social Death and Solitary Confinement: The Political Life of a Gerasene (Luke 8:26-39) - Menéndez Antuña, Luis (Journal of Biblical literature, 2019)
Characterization studies have recently experienced a revival through incorporation of interdisciplinary and processual analyses borrowed, in turn, from the broader field of literary studies. Studies on the Gospel of Luke exemplify a trend that, despite its increasing complexification of readerly strategies, continues to erase the role of real readers and contemporary communities of interpretation in the process of meaning making. In the present study, I offer an alternative to this deficit by analyzing, in intercontextual fashion, both the character of the Gerasene in Luke 8:26-39 and the experiences of prisoners in solitary confinement in the current US supermax prison system. I argue that the notion of social death shows that, in the Gerasene's and the prisoners' cases alike, relationality is the conditio sine qua non of subjectivity, and intersubjectivity is the condition of possibility of the political. The Gerasene, I conclude, transitions from an apolitical to a political status the moment another political animal (Jesus) steps into his domain.